| library /*isNonNullableByDefault*/; |
| import self as self; |
| import "dart:core" as core; |
| |
| class B<X extends core::Object? = dynamic, Y extends core::Object? = dynamic> extends core::Object { |
| synthetic constructor •() → self::B<self::B::X%, self::B::Y%> |
| ; |
| } |
| class C1<X extends (self::C1::Y) → self::C1::X = (Never) → dynamic, Y extends (self::C1::Y) → self::C1::X = (Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::C1<self::C1::X, self::C1::Y> |
| ; |
| } |
| class C2<X extends (self::C2::Y) → self::C2::X = (Never) → dynamic, Y extends (self::C2::X) → self::C2::Y = (Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::C2<self::C2::X, self::C2::Y> |
| ; |
| } |
| class C3<X extends (self::C3::X, self::C3::Y) → self::C3::X = (Never, Never) → dynamic, Y extends (self::C3::X, self::C3::Y) → self::C3::X = (Never, Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::C3<self::C3::X, self::C3::Y> |
| ; |
| } |
| class C4<X extends (self::C4::X, self::C4::Y) → self::C4::X = (Never, Never) → dynamic, Y extends (self::C4::X, self::C4::Y) → self::C4::Y = (Never, Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::C4<self::C4::X, self::C4::Y> |
| ; |
| } |
| class D1<X extends self::B<self::D1::X, self::D1::Y> = self::B<dynamic, dynamic>, Y extends (self::D1::Y) → self::D1::X = (Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::D1<self::D1::X, self::D1::Y> |
| ; |
| } |
| class D2<X extends self::B<self::D2::X, self::D2::Y> = self::B<dynamic, dynamic>, Y extends (self::D2::X) → self::D2::Y = (Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::D2<self::D2::X, self::D2::Y> |
| ; |
| } |
| class D3<X extends self::B<self::D3::X, self::D3::Y> = self::B<dynamic, dynamic>, Y extends (self::D3::X, self::D3::Y) → self::D3::X = (Never, Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::D3<self::D3::X, self::D3::Y> |
| ; |
| } |
| class D4<X extends self::B<self::D4::X, self::D4::Y> = self::B<dynamic, dynamic>, Y extends (self::D4::X, self::D4::Y) → self::D4::Y = (Never, Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::D4<self::D4::X, self::D4::Y> |
| ; |
| } |
| class E<X extends (self::E::X) → self::E::X = (Never) → dynamic> extends core::Object { |
| synthetic constructor •() → self::E<self::E::X> |
| ; |
| } |
| static field self::C1<(Never) → dynamic, (Never) → dynamic> c1; |
| static field self::C2<(Never) → dynamic, (Never) → dynamic> c2; |
| static field self::C3<(Never, Never) → dynamic, (Never, Never) → dynamic> c3; |
| static field self::C4<(Never, Never) → dynamic, (Never, Never) → dynamic> c4; |
| static field self::D1<self::B<dynamic, dynamic>, (Never) → dynamic> d1; |
| static field self::D2<self::B<dynamic, dynamic>, (Never) → dynamic> d2; |
| static field self::D3<self::B<dynamic, dynamic>, (Never, Never) → dynamic> d3; |
| static field self::D4<self::B<dynamic, dynamic>, (Never, Never) → dynamic> d4; |
| static field self::E<(Never) → dynamic> e; |
| static method main() → dynamic |
| ; |